The Body as a Resource in Psychotherapy - Beever, Rosemary (Auckland University of Technology, 2014)
The notion of “the body as a resource” implies a relationship to the body as a source of wisdom, guidance, strength and creativity. This research project explores this notion within psychotherapy using a hermeneutic literature review to examine relevant literature from both psychoanalysis and body psychotherapy. Body psychotherapy, and somatic trauma therapies, have a substantial knowledge base regarding the use and experience of the body as a resource. They privilege somatic awareness and experience, giving this a central place in the therapy process. Historically, psychoanalysis has largely ignored this aspect of the body, despite Freud’s initial focus on body based drives. However, contemporary psychoanalysis and psychodynamic psychotherapy, influenced by intersubjectivity, affective neuroscience and trauma therapy, are increasingly acknowledging the body. Somatic countertransference in particular is seen as an important resource. This dissertation reviews literature from all of these approaches, comparing, contrasting and synthesising the wisdom they offer regarding the body as a resource; thus contributing to the growing cross-fertilisation between these historically separate disciplines. In keeping with its hermeneutic approach, it incorporates some of the writer’s subjective responses to the literature. This dissertation provides an account of the history of the body in psychotherapy, and examines the developmental basis for the body as a resource, with reference to psychodynamic and bioenergetic theory and affective neuroscience, before going on to describe how the body is experienced and used in this way, via three main themes: awareness, communication and shifting states. “Awareness” examines the centrality of embodied self-awareness to the topic, looking at practices which can develop and sustain this capacity. “Communication” describes an intersubjective approach to the body within psychotherapy, and outlines various understandings of somatic communication, particularly the notion of somatic counter-transference. “Shifting states” describes some somatic interventions used in body psychotherapy to generate therapeutic change. It goes on to outline three major approaches to somatic trauma therapy; and finally, it explores the notion of therapist self-resourcing. This dissertation explores how therapists may use their body as a resource in their clinical practice, and how they may support clients to develop this kind of relationship to their own bodies. It proposes that an embodied, relational approach to psychotherapy facilitates the capacity to experience and use the body as a resource.
Keywords: Somatic; Body awareness; Body psychotherapy; Psychodynamic psychotherapy; Hermeneutic literature review; Bioenergetics; Self-regulation; Dyadic regulation; Somatic resource; Somatic countertransference; Relational body psychotherapy